Pengaruh Biaya Modal dan Profitabilitas Terhadap Nilai Saham Bank BTPN Syariah Periode 2018-2020 - Siska Yuli Anita (Politeknik Ganesha Medan, 2022)
Operations and investments of Islamic banks certainly require capital as the foundation and start of the bank's business, so estimating the cost of capital required is an important process and good corporate profits will provide a good image for the company. This study aims to determine the effect of capital with the Weighted Average Cost Of Capital (WACC) method on stock values. The effect of profitability with the ratio of Return On Equity (ROE) on stock value. And the effect of the cost of capital and profitability on the value of the stock. This study uses a descriptive quantitative research method. By using secondary data in the form of monthly financial statements of Bank BTPN Syariah for the 2018-2020 period. All of these data are materials for estimating and calculating the cost of capital and profitability of Bank BTPN Syariah. The results showed that partially the cost of capital had a significant positive effect on the stock value, profitability had a significant negative effect on the stock value. Meanwhile, simultaneously the cost of capital and profitability affect the value of the stock.